SAT0744-HPR Prevalence of commorbidities in patients with rheumatoid arthritis and correlation with disease activity and type of therapy. (12th June 2018) - Cabrera, M.; Villarreal, L.; Buitrago-Garcia, D.; Santos-Moreno, P.
Abstract : Background: Rheumatoid arthritis (RA) is a common systemic autoimmune disease characterised chronic joint inflammation. Patients with RA are also reported to have higher prevalence of comorbidities such as cardiovascular disease, osteoporotic among others. 1 These comorbidities can be associated with higher mortality, poor life quality, and the increasing of costs for the health system. Objectives: To describe the prevalence of comorbidities and characteristics of a Colombian population that assist to a RA specialised centre. Methods: We performed a descriptive analysis; our main goal was to provide real-life data regarding characteristics of patients with RA. We collected sociodemographic information, DAS28, and prevalence of comorbidities regarding hypertension, cerebrovascular disease, diabetes mellitus, osteoporosis, renal chronic disease, or Sjogren's syndrome. We calculated means, and standard deviations for continuous variables and categorical variables were presented as rates. We estimated the prevalence of comorbidities and evaluate independent associations calculating prevalence ratios. Results: 6376 patients were included in the analysis; mean age was 59 years±12, 81% were woman and 19% were men. Mean DAS28 was 2.8±1.07. From all patients the prevalence of comorbidities was 42% hypertension, cerebrovascular disease, diabetes mellitus, osteoporosis, renal chronic disease, or Sjogren's syndrome. Most of these patients 60% reported to have hypertension with any of the others comorbidities mentioned above, or osteoporosis with other comorbidities 46%. Regarding pharmacological therapy a higher proportion of patients received conventional DMARDs 90% see table 1. The prevalence of comorbidities was associated with sex and disease activity but did not have any association with pharmacological therapy see table 2. Conclusions: As other studies conducted in Asian or Australian populations high blood pressure is the most common disease among patients with RA followed by osteoporosis(. 1 Sex is associated with higher comorbidities. According to these results it is important to consider the patient's context, medical conditions, and the number of comorbidities in order to understand the complexity of the management of patient with RA. Reference: [1] Jin S, Li M, Fang Y, Li Q, Liu J, Duan X, et al. Chinese Registry of rheumatoid arthritis (CREDIT): II. prevalence and risk factors of major comorbidities in Chinese patients with rheumatoid arthritis. Arthritis research & therapy2017;19(1):251. Disclosure of Interest: None declared